Implementasi Akuntansi Pajak Pertambahan Nilai pada Pengadaan Suku Cadang di Lingkungan PT. Kereta Api Indonesia (Persero) Divre I SU Bengsar Pulo Brayan - Agung Nugroho (CERED Indonesia Institute, 2020)
The purpose of this study was to determine and analyze the system and application of VAT accounting in the procurement of spare parts at PT. Kereta Api Indonesia (Persero) Divre I SU Bengsar Pulobrayan as well as the implications of the system and application of VAT accounting for companies in the procurement of spare parts at PT. Kereta Api Indonesia (Persero) Divre I SU Bengsar Pulobrayan. The study was conducted at PT. Indonesian Railways Regional Division I North Sumatra Bengsar Pulobrayan, which is a State-Owned Enterprise (BUMN) which is engaged in transportation. The research approach used is descriptive research. The results of this study illustrate that the VAT policy at PT. Kereta Api Indonesia (Persero) Division I SU Bengsar Pulobrayan regulated in PMK No. 80 of 2012 where railroad transportation services are not subject to VAT, except for rent or charter. Implications of the publication of PMK No. 80 of 2012 brought influence to the government and PT. KAI For the government, the elimination of VAT on freight services in the form of short-term freight trains could reduce the country's revenue from VAT. With the existence of KMK 80 of 2012, it is expected to reduce logistics costs and improve the competitiveness of other modes of transportation such as road transport. For PT KAI, the implications of this policy can provide administrative convenience and are expected to encourage the railroad industry in transportation activities.